A single-source precursor approach to solution processed indium arsenide thin films. Issue 28 (28th June 2016) - Marchand, Peter; Sathasivam, Sanjayan; Williamson, Benjamin A. D.; Pugh, David; Bawaked, Salem M.; Basahel, Sulaiman N.; Obaid, Abdullah Y.; Scanlon, David O.; Parkin, Ivan P.; Carmalt, Claire J.
Abstract : Highly crystalline, stoichiometric InAs films have been deposited utilising a novel InAs cluster as a single source precursor. Abstract : This paper reports the synthesis of the novel single-source precursor, [{(MeInAs t Bu)3 }2 (Me2 InAs( t Bu)H)2 ] and the subsequent first report of aerosol-assisted chemical vapour deposition of InAs thin films. Owing to the use of the single-source precursor, highly crystalline and stoichiometric films were grown at a relatively low deposition temperature of 450 °C. Core level XPS depth profiling studies showed some partial oxidation of the film surface, however this was self-limiting and disappeared on etch profiles. Valence band XPS analysis matched well with the simulated density of state spectrum. Hall effect measurements performed on the films showed that the films were n-type with promising resistivity (3.6 × 10 −3 Ω cm) and carrier mobility (410 cm 2 V −1 s −1 ) values despite growth on amorphous glass substrates.